Comparative analysis between two GT4 glycosyltransferases related to polysaccharide biosynthesis in Rhodococcus jostii RHA1 - Cereijo, Antonela Estefanía (2023)
The bacterial genus Rhodococcus comprises organisms that perform an oleaginous behavior under certain growth conditions and the ratio of carbon and nitrogen availability. Thus, Rhodococcus spp have outstanding biotechnological features as microbial producers of biofuel precursors, which would be used instead of lipids from crops. It was postulated that lipid and glycogen metabolism in Rhodococci are closely related. Thus, a better understanding of rhodococcal carbon partitioning requires identifying the catalytic steps redirecting sugar moieties to temporal storage molecules, such as glycogen and trehalose. In this work, we analyzed two glycosyl-transferases GT4 from R. jostii, RjoGlgAb and RjoGlgAc, which were annotated as α-glucan-α-1,4-glucosyl transferases, putatively involved in glycogen synthesis. Both enzymes were recombinantly produced in E. coli BL21 (DE3) cells, purified to near homogeneity, and kinetically characterized. RjoGlgAb and RjoGlgAc presented the “canonical” glycogen synthase (EC 2.4.1.21) activity. Besides, both enzymes were actives as maltose-1P synthases (GlgM, EC 2.4.1.342), although to a different extent. In this scenario, RjoGlgAc is a homologous enzyme to the mycobacterial GlgM, with similar behavior regarding kinetic parameters and glucosyl-donor (ADP-glucose) preference. RjoGlgAc was two orders of magnitude more efficient to glucosylate glucose-1P than glycogen. Also, this rhodococcal enzyme used glucosamine-1P as a catalytically efficient aglycon. On the other hand, both activities exhibited by RjoGlgAb depicted similar kinetic efficiency and a preference for short-branched α-1,4-glucans. Curiously, RjoGlgAb presented a super-oligomeric conformation (higher than 15 subunits), representing a novel enzyme with a unique structure to function relationships. Results presented herein constitute a milestone regarding polysaccharide biosynthesis in Actinobacteria, leading to (re)discovery of methyl-glucose lipo-polysaccharide metabolism in Rhodococci.